Chế tạo vật liệu compozit sinh học trên nền nhựa polyvinyl ancol gia cường bằng sợi nứa - Diệu, Trần Vĩnh; Minh Ngọc, Phan Thị; Yến Oanh, Đoàn Thị; Chiến, Lê Cao; Đức, Vũ Minh (Vietnam Journal of Chemistry, 2014)
After extracting by machine method, Neohouzeaua dulloa fiber was treated by alkali 1 N solution, within 2 hours at temperature 90oC. The testing on the interfacial shear strength showed that with treated fiber was increased 23.6% compared to untreated one. The tensile, flexural and impact strengths of polymer composites (PC) were improved 444%, 75% and 161% respectively compared to PC-untreated one. The effect of concentration of polyvinyl alcohol solution on composites was carried out. The results revealed that, at concentration of 12%, the composite was easier to manufacture and processed potential mechanical properties. The effect of pentaetythritol and polyetylenglycol contents on mechanical properties of PC was carried out. The results showed that at the content of 13% pentaerythritol and 7% polyethyleneglycol, the received materials processes potential properties and easy to manufacture.